Social Commerce Optimization for Banyumas MSMEs on Shopee and Tokopedia: A Mixed-Methods Approach - Rizqi Faturohman; Dhanar Intan Surya Saputra; Retno Waluyo (Journal of Computers and Digital Business, 2026)
The development of social commerce has accelerated the transformation of the digital business ecosystem for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly through marketplace platforms such as Shopee and Tokopedia. This study aims to analyze the effect of social commerce optimization on the competitiveness of MSMEs in Banyumas Regency and identify strategic factors supporting digital business transformation. The research employed a mixed-methods approach with a sequential explanatory design integrating quantitative and qualitative methods. Quantitative data were collected through questionnaires distributed to 120 MSMEs actively using Shopee and Tokopedia, while qualitative data were obtained through semi-structured interviews with 12 informants consisting of MSME actors, digital marketing practitioners, MSME communities, and academics. The results of simple regression analysis indicate that social commerce significantly affects MSME competitiveness (β = 0.684; p < 0.001), with a coefficient of determination (R²) of 0.468, indicating that social commerce contributes 46.8% to improving MSME competitiveness. The findings reveal that live shopping features, affiliate marketing, customer reviews, and social media integration significantly enhance customer engagement, digital branding, and market expansion. This study contributes to the development of a social commerce optimization framework based on customer engagement and digital branding to strengthen MSME competitiveness within the digital economic ecosystem.